2009
DOI: 10.1111/j.1463-5224.2009.00717.x
|View full text |Cite
|
Sign up to set email alerts
|

Daytime profile of the intraocular pressure and tear production in normal dog

Abstract: This study has demonstrated circadian rhythms in both IOP and STT I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(87 citation statements)
references
References 19 publications
6
73
1
Order By: Relevance
“…50 This effect of cross-linking deficiency may partially explain the decreased mechanical damping properties (i.e., tan [d]) in the affected canine sclera, because the decreased intrafibril sliding in the lesser cross-linked group effectively would reduce the relative amount of energy dissipated by the fibrils. The measurements before euthanasia showed that all IOP values (11-17 mm Hg) were well within the normal range of IOPs seen in clinically healthy dogs, [51][52][53] confirming that the young affected dogs still were normotensive. Although not statistically significant, the mean IOP at euthanasia was slightly higher in the young affected dogs compared to that in the young carrier dogs (16.0 6 1.4 vs. 13.5 6 2.1 mm Hg), prompting a consideration of whether this IOP could have confounded the outcome of the genotype comparisons reported in our study.…”
Section: Discussionmentioning
confidence: 92%
“…50 This effect of cross-linking deficiency may partially explain the decreased mechanical damping properties (i.e., tan [d]) in the affected canine sclera, because the decreased intrafibril sliding in the lesser cross-linked group effectively would reduce the relative amount of energy dissipated by the fibrils. The measurements before euthanasia showed that all IOP values (11-17 mm Hg) were well within the normal range of IOPs seen in clinically healthy dogs, [51][52][53] confirming that the young affected dogs still were normotensive. Although not statistically significant, the mean IOP at euthanasia was slightly higher in the young affected dogs compared to that in the young carrier dogs (16.0 6 1.4 vs. 13.5 6 2.1 mm Hg), prompting a consideration of whether this IOP could have confounded the outcome of the genotype comparisons reported in our study.…”
Section: Discussionmentioning
confidence: 92%
“…Horizontal pupil diameter was measured with Jameson calipers under fixed light conditions every five minutes as described above. All measurements were done at approximately same time of day (9.00-11.00 am) because of the effects of light conditions at different times of day on the IOP and the HPD (Gelatt et al, 1981;Giannetto et al, 2009).…”
Section: Datamentioning
confidence: 99%
“…Ulcer depth was entered as an ordinal variable from 0 (no ulcer) to 3 (deep ulcer), with STT and IOP as covariates. Given the mean value of 20±3 mm/min from normal dogs in one paper from the senior author's research group (Hartley et al, 2006) and 20±1 mm/min in a paper from another group (Giannetto et al, 2009) a power calculation showed that detecting a 3mm/min difference between ulcerated and control eyes with a statistical power of 0.8 and significance at 0.05 would require 30 cases. Similarly detecting a difference of 5mmHg in dogs with a mean and standard deviation of 19±6 mmHg, a figure derived from a previous published large sample of normal dogs (Giannetto et al, 2009), would require a sample size of 36 dogs.…”
Section: Introductionmentioning
confidence: 99%
“…There were no significant differences between eyes with signs of mild inflammation, as noted above, and those without. The study makes the assumption that there is no significant difference in STT or IOP between the right and left eyes, this based on the fact that previous studies have not shown a difference between STT values of left and right eyes in normal dogs (Wyman et al, 1995), and similarly IOP values have not been shown to differ between eyes (Giannetto et al, 2009) so we feel confident that differences between ulcerated and control eyes here are highly likely to be related to the ulceration and not a random difference between eyes. One limitation of this study was to only perform the Schirmer I test which measures both basal and reflex tear production.…”
mentioning
confidence: 99%